Functioning of inclusion classrooms in the opinion of parents – organization, teacher training, individualized instruction and social relations - PRZYBYSZEWSKA, DOMINIKA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Dominika Przybyszewska, Functioning of inclusion classrooms in the opinion of parents – organization, teacher training, individualized instruction and social relations. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 83-108. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.05 Inclusive education is one of the available forms of education for students with disabilities in Poland. Inclusion classrooms have fewer student and an additional teacher assistant. The schools in which this type of education takes place should meet a number of requirements. They start with the infrastructure and available teaching aids, and end with the teacher training and the availability of specialists. However, these are only prerequisites. In addition to them, the attitude of teachers and their training, the atmosphere prevailing in the school and the relations between students are important. All these elements are components on which success depends. The article presents the opinions of parents whose children attend such classes. Their voice is consistent with the results obtained by other researchers and the reports of the Supreme Audit Office (NIK)- there are no teaching aids, it is not always possible to talk to specialists (staff shortages), the individualization used in working with students is insufficient, and the relations in classes are only seemingly good.